Osteoclasts and Macrophages—Their Role in Bone Marrow Cavity Formation During Mouse Embryonic Development. (5th July 2022) - Tosun, Benjamin; Wolff, Lena Ingeborg; Houben, Astrid; Nutt, Stephen; Hartmann, Christine
ABSTRACT: The formation of the bone marrow cavity is a prerequisite for endochondral ossification. In reviews and textbooks, it is occasionally reported that osteoclasts are essential for bone marrow cavity formation removing hypertrophic chondrocytes. Mice lacking osteoclasts or having functionally defective osteoclasts have osteopetrotic bones, yet they still form a bone marrow cavity. Here, we investigated the role of osteoclasts and macrophages in bone marrow cavity formation during embryogenesis. Macrophages can assist osteoclasts in matrix removal by phagocytosing resorption byproducts. Rank ‐deficient mice, lacking osteoclasts, and Pu.1 ‐deficient mice, lacking monocytes, macrophages, and osteoclasts, displayed a delay in bone marrow cavity formation and a lengthening of the zone of hypertrophic chondrocytes. F4/80‐positive monocyte/macrophage numbers increased by about fourfold in the bone marrow cavity of E18.5 Rank ‐deficient mice. Based on lineage‐tracing experiments, the majority of the excess F4/80 cells were derived from definitive hematopoietic precursors of the fetal liver. In long bones of both Rank −/− and Pu.1 −/− specimens, Mmp9‐positive cells were still present. In addition to monocytes, macrophages, and osteoclasts, Ctsb‐positive septoclasts were lost in Pu.1 −/− specimens. The mineralization pattern was altered in Rank −/− and Pu.1 −/− specimens, revealing a significant rise in transverse‐oriented mineralized structures. Taken together, our findings imply that early on during bone marrow cavity formation, osteoclasts facilitate the entry of blood vessels and later the turnover of hypertrophic chondrocytes, whereas macrophages appear to play no major role. Furthermore, the absence of septoclasts in Pu.1 −/− specimens suggests that septoclasts are either derived from Pu.1‐dependent precursors or require PU.1 activity for their differentiation. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).